A 21st-century renaissance of kites as platforms for proximal sensing. (April 2016) - Duffy, James P.; Anderson, Karen
In 1903, WH Dines first proposed kites as platforms from which scientific measurements could be captured. This early paper was focused on the collection of atmospheric measurements but later on, kites were used widely as platforms for aerial photography – a memorable example is the aerial survey of San Francisco captured from a kite platform after the 1906 earthquake. In this paper, we begin by providing a brief overview of this early scientific and remote sensing work from kite platforms. We then discuss the resurgence of kite use within modern geography and environmental science research using examples from published work in the past 20 years. We discuss how the use of kites in these disciplines has expanded in recent years, with a renewed focus on the collection of proximal remote sensing data. Also, we present a variety of contemporary examples of kite-based sensing (including basic mapping, ecological survey, population counts and humanitarian mapping) and discuss the merits of kites compared to drone-based platforms which have captured much of the public and scientific attention as proximal sensing platforms in recent times. The beauty of kite-based proximal sensing lies in the simplicity and low-cost nature of data capture, as highlighted by Dines' 1903 paper. This simplicity supported by the wide array of modern complex data processing capabilities means that kites are now in a position to deliver fine-grained spatial data to the modern geographer. Furthermore, in today's world, there are many situations where kites can fly freely, but drones cannot.